Editorial note: The State Of Malaysian security and strategic studies during Covid-19 pandemic - Zarina Othman,; Bakri Mat, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This year marked the second year of SINERGI: Journal of Strategic Studies & International Affairs' publication and endeavoured to exhibit both local and international, as well as senior and junior writers in Politics, Strategic, Defence and International Affairs. Simultaneously, 2022 is a transition year towards post-pandemic. There is no doubt that concerted transnational efforts in dealing with the security threats of the pandemic Covid-19 have intertwined with a growing research agenda in understanding the nexus between pandemic and Strategic Studies. The threats of infectious diseases to human health and economic activity have caused an intensification and an organisational formalisation of Malaysian health diplomacy, both regionally and bilaterally. Such diplomacy has also established a basis for developing a wider set of cooperative relationships that go beyond responding to the threat of pandemics. As Malaysia approaches “developed” status, its health sector is becoming increasingly integrated into the global political economy through transnational joint research and development and international relations ventures.